First case of pulmonary acariasis in a pig-tailed macaque in Malaysia - Mazlan, Mazlina; Shamsudin, Shahirudin; Moktar, Maizatul Akma; Sharma, Reuben Sunil Kumar (Universiti Putra Malaysia Press, 2010)
A 15 year-old male, southern pig-tailed macaque (Macaca nemestrina), was found to have a history of bloody urine, inappetance, weight loss, and was weak before death. Multiple yellow to gray nodular-like lesions were observed grossly all over the lung. Some of the nodules were flattened and some were raised and there were also cavitations and tubercles-like lesions on the cut surface. Histopathologically, focal granulomatous lesions were seen throughout the lungs, especially those with the presence of mites. There were moderate alveolar macrophages observed with mild eosinophilic, plasma cells, and slight lymphocytes and neutrophilic cells infiltration. There was also the presence of the brownish mite pigments in the lung tissue as well as in macrophages. Diagnosis was made from the morphological observation of intact mites isolated from lung tissues. This is the first report on pulmonary acariasis in Malaysia.